Metabolomic profiling of triple negative breast cancer cells suggests that valproic acid can enhance the anticancer effect of cisplatin - Granit, Avital; Mishra, Kumudesh; Barasch, Dinorah; Peretz-Yablonsky, Tamar; Eyal, Sara; Kakhlon, Or (Frontiers in Cell and Developmental Biology, 2022)
Cisplatin is an effective chemotherapeutic agent for treating triple negative breast cancer (TNBC). Nevertheless, cisplatin-resistance might develop during the course of treatment, allegedly by metabolic reprograming, which might influence epigenetic regulation. We hypothesized that the histone deacetylase inhibitor (HDACi) valproic acid (VPA) can counter the cisplatin-induced metabolic changes leading to its resistance. We performed targeted metabolomic and real time PCR analyses on MDA-MB-231 TNBC cells treated with cisplatin, VPA or their combination. 22 (88%) out of the 25 metabolites most significantly modified by the treatments, were acylcarnitines (AC) and three (12%) were phosphatidylcholines (PCs). The most discernible effects were up-modulation of AC by cisplatin and, contrarily, their down-modulation by VPA, which was partial in the VPA-cisplatin combination. Furthermore, the VPA-cisplatin combination increased PCs, sphingomyelins (SM) and hexose levels, as compared to the other treatments. These changes predicted modulation of different metabolic pathways, notably fatty acid degradation, by VPA. Lastly, we also show that the VPA-cisplatin combination increased mRNA levels of the fatty acid oxidation (FAO) promoting enzymes acyl-CoA synthetase long chain family member 1 (ACSL1) and decreased mRNA levels of fatty acid synthase (FASN), which is the rate limiting enzyme of long-chain fatty acid synthesis. In conclusion, VPA supplementation altered lipid metabolism, especially fatty acid oxidation and lipid synthesis, in cisplatin-treated MDA-MB-231 TNBC cells. This metabolic reprogramming might reduce cisplatin resistance. This finding may lead to the discovery of new therapeutic targets, which might reduce side effects and counter drug tolerance in TNBC patients.